Physicochemical properties and sensory acceptability of goat’s milk fruit yogurts with mango and banana using accelerated testing - Vásquez-Villalobos, Víctor (2015)
Two types of skimmed (fat 3%) goat’s milk fruit yogurt with mango (YM) and banana (YB) were stored at temperatures of 5 °C, 15 °C and 25 °C for 72 hours. Every 24 hours the pH, titratable acidity, total solids, fat and protein were analyzed. Sensory acceptability was also evaluated with 75 yogurt frequent consumers, who responded with "yes" or "no" to the question ¿would you consume this product? At the beginning pH, acidity, total solids, fat and protein were 4.35 and 4.36; 0.76% and 0.75%; 12.71% and 13.23%; 3.2% and 3.3%; 4.4% and 4.5%, for the YM and YB respectively, meeting known standards for cow's milk yogurt: range of acidity 0.5%-1.6%, fat maximum value 15% and protein minimum value 2.7%. The sensory acceptability of the YM and the YB was high, with 88.9% and 94.7%, respectively. During storage under accelerated conditions, pH decreased to 3.88 and 3.92; titrable acidity increased to 1.1% and 0.93%; total solids, fat and protein decreased to 9.37% and 9.7%; 2.4% and 2.0%; 2.5% and 2.6%, for the YM and YB respectively, while remaining within the limits of the standards consulted. The sensory acceptability decreased to 4% and 5.33% for YM and YB respectively. Therefore the shelf life of the sensory acceptability was estimated (S.S.A) at 4°C in a rejection percentage of 25% and 50%, 69 and 49 h; 193 and 111 h, for the YM and YB respectively.